Transcriptome-Wide Analysis Reveals Modulation of Human Macrophage Inflammatory Phenotype Through Alternative Splicing. Issue 7 (July 2016) - Lin, Jennie; Hu, Yu; Nunez, Sara; Foulkes, Andrea S.; Cieply, Benjamin; Xue, Chenyi; Gerelus, Mark; Li, Wenjun; Zhang, Hanrui; Rader, Daniel J.; Musunuru, Kiran; Li, Mingyao; et al.
Abstract : Objective—: Human macrophages can shift phenotype across the inflammatory M1 and reparative M2 spectrum in response to environmental challenges, but the mechanisms promoting inflammatory and cardiometabolic disease–associated M1 phenotypes remain incompletely understood. Alternative splicing (AS) is emerging as an important regulator of cellular function, yet its role in macrophage activation is largely unknown. We investigated the extent to which AS occurs in M1 activation within the cardiometabolic disease context and validated a functional genomic cell model for studying human macrophage-related AS events. Approach and Results—: From deep RNA-sequencing of resting, M1, and M2 primary human monocyte–derived macrophages, we found 3860 differentially expressed genes in M1 activation and detected 233 M1-induced AS events; the majority of AS events were cell- and M1-specific with enrichment for pathways relevant to macrophage inflammation. Using genetic variant data for 10 cardiometabolic traits, we identified 28 trait-associated variants within the genomic loci of 21 alternatively spliced genes and 15 variants within 7 differentially expressed regulatory splicing factors in M1 activation. Knockdown of 1 such splicing factor, CELF1, in primary human macrophages led to increased inflammatory response to M1 stimulation, demonstrating CELF1's potential modulation of the M1 phenotype. Finally, we demonstrated that an induced pluripotent stem cell–derived macrophage system recapitulates M1-associated AS events and provides a high-fidelity macrophage AS model. Conclusions—: AS plays a role in defining macrophage phenotype in a cell- and stimulus-specific fashion. Alternatively spliced genes and splicing factors with trait-associated variants may reveal novel pathways and targets in cardiometabolic diseases. Abstract : Supplemental Digital Content is available in the text.